The Joint Roles of the Executive Governmental Functionaries in Enhancing the Islamic Economics System - Md Nor, Mohd Zakhiri (American Scientific Publishers, 2017)
One of the important components of the administration of the State is the executive governmental functionaries. These functionaries execute and implement the rules and regulations prescribed upon them, either by the written rules or customary law. This paper provides an account for the structural executive governmental functionaries and their major roles in enhancing the Islamic economics system in carefully chosen case studies for the purpose of this paper: Malaysia, Saudi Arabia, Pakistan and Sudan as comparative analysis. The methodology used in this paper is doctrinal which is library-based in nature. This paper highlights that the joint roles of these functionaries, albeit the different country backgrounds and legal framework, all work in unison towards enhancing the Islamic economics system in the respective jurisdictions.